2009
DOI: 10.1093/carcin/bgp064
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of astrocyte elevated gene-1 (AEG-1) is associated with esophageal squamous cell carcinoma (ESCC) progression and pathogenesis

Abstract: Astrocyte elevated gene-1 (AEG-1), upregulated in various types of human cancers, has been reported to be associated with the carcinogenesis of human cancer. However, the functional significance of AEG-1 in human esophageal squamous cell carcinoma (ESCC) remains unknown. In the present study, we showed the expression of AEG-1 was markedly upregulated in esophageal cancer cell lines and surgical ESCC specimens at both transcriptional and translational levels. Immunohistochemical analysis revealed that 80 of 168… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
168
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 36 publications
14
168
1
Order By: Relevance
“…32 Overexpression of AEG-1/MTDH was observed in many types of cancers, such as malignant astrocytoma, 33 neuroblastoma, 34 and cancers of esophagus, 35 breast, 36 prostate 37 and liver. 38 Many reports have indicated that AEG-1/MTDH contributes to several steps in human oncogenesis, including cancer-cell progression, invasion, metastasis and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…32 Overexpression of AEG-1/MTDH was observed in many types of cancers, such as malignant astrocytoma, 33 neuroblastoma, 34 and cancers of esophagus, 35 breast, 36 prostate 37 and liver. 38 Many reports have indicated that AEG-1/MTDH contributes to several steps in human oncogenesis, including cancer-cell progression, invasion, metastasis and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of AEG-1 was observed in melanoma (Kang et al, 2005), glioma (Kang et al, 2005), neuroblastoma (Lee et al, 2009), and carcinomas of breast (Li et al, 2008), prostate (Kikuno et al, 2007), esophagus (Yu et al, 2009), stomach (Jian-bo et al, 2011 and liver (Yoo et al, 2009), which was correlated with poor clinical outcomes. It was reported that AEG-1 was overexpressed in 490% of human HCC compared with normal liver and had a central role in regulating diverse aspects of HCC pathogenesis (Yoo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, clinical studies have revealed that MTDH is overexpressed in various malignancies, including breast, prostate, glioma, hepatocellular, and esophageal cancer and is associated with disease progression and poor clinical outcomes (14). Moreover, MTDH has been found to promote cancer metastasis, chemoresistance, invasion and angiogenesis (15)(16)(17)(18)(19)(20)(21), suggesting that it may function as an oncogene. Furthermore, MTDH knockdown has been found to sensitize breast cancer and neuroblastoma cells to cisplatin (15,17).…”
Section: Introductionmentioning
confidence: 99%